Pengaruh Lembaga Swadaya Masyarakat/Ormas Dalam Hal Mempertahankan Pasal 28e Ayat 3 Uud 1945 - Irwan Polidu; Cindy Oktaviany Pepa (LPPM Universitas Bina Taruna Gorontalo, 2023)
The influence of non-governmental organizations/mass organizations in maintaining article 28e paragraph 3 of the 1945 Constitution: every person has the right to freedom of association, assembly and expression of opinion. The aim of this research is to analyze the extent of the influence of non-governmental organizations/mass organizations in maintaining article 28e paragraph 3 of the 1945 Constitution. Every person has the right to freedom of association, assembly and expression in Indonesia today. The research method used is normative juridical research. Based on the results of the research in writing the article above, it can be concluded that how important it is to maintain this country's constitution, with the existence of Law Number 17 of 2013 concerning social organizations, the public is clearly and legally free to express opinions in public in terms of safeguarding the unitary state of the Republic of Indonesia into a country that is advanced in terms of government administration, not only that, the community can exercise social control freely from remote areas to the central level without any further intervention and discrimination from irresponsible elements in this country.